Pengaruh Abu Limbah Kandang Ayam Dan Varietas Terhadap Pertumbuhan,Hasil, Dan Kemunculan Blossom End Rot Pada Tanaman Tomat Di Tanah Gambut - keti, keti (Jurnal Sains Pertanian Equator, 2014)
THE EFFECT OF THE ASH FROM CHICKEN COOP WASTE AND VARIETIES ON GROWTH, YIELD AND APPEARANCE OF BLOSSOM END ROT OF TOMATOES IN PEAT SOIL Keti (1), Nurjani (2), Sholahuddin(2) (1) Student Of Agriculture Faculty Of Tanjungpura University (2) The Lecturer Of Agriculture Faculty Of Tanjungpura University ABSTRACT The purpose of this research is to know the interaction between the ash of chicken coop waste and tomato varieties on growth, yield and appearance of Blossom End Rot in peat soil. The study was conducted in Kalimas village, Kakap subdistric, Kubu Raya distric, from April to July 2013. The method was a field experiment with factorial pattern Completely Randomized Design (CRD) consists of 2 factors which is the ash from chicken coop waste as (0kg, 1,3kg, 1,8kg, 2,3kg) and varieties of plants (Permata dan Tymoti). Observed variables were the dry weight plants (g), the flowering ages (dap), the harvest age (dap), the plant heights (cm), the fruit set per plant (fruit set), the fruit number per plant (fruits), the fruit weight per plant (g), the fruits number attacked by BER (fruits), and the percentage of yield reduction due to BER (%). The results showed that supply of ash chicken coop waste in peat soil does not make a difference on the growth and yield of tomato plants. The use Tymoti varieties tend to give better results than Permata. The study revealed that the ash of chicken coop waste and varieties have not been able to suppress the appearance of Blossom End Rot (BER) on tomato plants in peat soil. The interaction of both are shown only on the amount of tomato fruits set. Key words : Ash, Blossom End Rot, Peat soil, Tomato.